Small regulatory RNAs in Streptococcus pneumoniae: discovery and biological functions - Wilton, Joana; Acebo, Paloma; Herranz, Cristina; Gómez, Alicia; Amblar, Mónica (Frontiers in Genetics, 2015)
Streptococcus pneumoniae is a prominent human pathogen responsible for many severe diseases and the leading cause of childhood mortality worldwide. The pneumococcus is remarkably adept at colonizing and infecting different niches in the human body, and its adaptation to dynamic host environment is a central aspect of its pathogenesis. In the last decade, increasing findings have evidenced small RNAs (sRNAs) as vital regulators in a number of important processes in bacteria. In S. pneumoniae, a small antisense RNA was first discovered in the pMV158 plasmid as a copy number regulator. More recently, genome-wide screens revealed that the pneumococcal genome also encodes multiple sRNAs, many of which have important roles in virulence while some are implicated in competence control. The knowledge of the sRNA-mediated regulation in pneumococcus remains very limited, and future research is needed for better understanding of functions and mechanisms. Here, we provide a comprehensive summary of the current knowledge on sRNAs from Streptococcus pneumoniae, focusing mainly on the trans-encoded sRNAs.